TOPONIMI DUMASAR CARITA RAHAYAT DI KACAMATAN PARIGI KABUPATÉN PANGANDARAN PIKEUN BAHAN PANGAJARAN DONGÉNG DI KELAS VII SMP - Intan Nur, - (2019)
Latar belakang penelitian ini adalah adanya kekhawatiran peneliti akan ketiaktahuan mengenai toponimi yang berkaitan dengan cerita rakyat. Penelitian ini bertujuan untuk mendeskripsikan: 1) pola penamaan tempat di Kacamatan Parigi Kabupaten Pangandaran; 2) toponimi dusun di Kacamatan Parigi Kabupaten Pangandaran;dan 3) analisis bahan ajar dongeng di kelas VII SMP. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Hasilnya: dari 53 dusun yang teranalisis ada 33 (62%) nama dusun yang dipengaruhi oleh aspek fisikal terbagi menjadi tiga unsur yaitu:22 nama dusun termasuk ke dalam unsur hidrologis, 5 nama dusun termasuk ke dalam aspek geomorfologis dan 6 nama dusun termasuk ke dalam unsur biologi. Ada 20 (38%) nama dusun yang dipengaruhi oleh aspek non fisikal terbagi menjadi dua unsur yaitu: 17 nama dusun dipengaruhi oleh unsur sosial, serta 3 nama dusun dipengaruhi oleh unsur kultural. Dari 53 nama dusun, 12 nama dusun memakai pola toponimi linear dan 41 nama dusun memakain pola toponimi gabungan. Pola toponimi gabungan terbagi menjadi 4 pola(hidrologis+X, géomorfologis+X, biologis flora+X, jeung sosial+X) yang terbagi lagi menjadi beberapa subpola yaitu: 7 subpola toponimi hidrologis, 4 subpola toponimi géomorofologis, 2 subpola toponimi biologis flora, jeung 4 subpola toponimi sosial. Dari 53 cerita yang teranalisis, ada 7 dongeng yang cocok untuk bahan ajar dongeng serta sesuai dengan kriteria memilih bahan ajar. Kata kunci: toponimi, cerita rakyat, bahan ajar dongeng, Kacamatan Parigi Kabupaten Pangandaran. ------ The background of this research is the concern of researchers about the disappearance of folklore in Parigi Sub-District. This research aim to describes: 1) the naming pattern in Parigi Sub-District Pangandaran District; 2) toponymy of village in Parigi Sub-District, Pangandaran District, and 3) fairy-tale teaching materialsanalysis in class VII SMP. The method used in this research is descriptive qualitative. The result are: from 53 villages that have been analyzed, 33 (62%) villages names which affected by physical aspects are divided into three elements; 22 villages have been classified into hydrological element, 5 villages have been classified into geomorphological aspect and 6 villages have been classified into biological elements. There are 20 (38%) villages which named by non-physical aspects divided into two elements, which are: 17 villages have been classified into social elements, and 3 villageshave been classiefied into cultural elements. From 53 villages that have been analyzed, 12 village names use a linear toponymy pattern and 41 village names use a combined toponymy pattern. The combined toponymy pattern is divided into 4 patterns (hydrological + X, géomorphological + X, biological flora + X, social jeung + X) which are further divided into several sub-patterns, namely: 7 hydrological toponimi sub-patterns, 4 gonomorphological topographic sub-patterns, 2 biological topographic sub-patterns; jeung 4 social toponymy sub-pattern. From 53 analyzed stories, there are 7 fairy tales that are suitable for fairy tale teaching materials also suitable for choosing the criteria of teaching material. Keywords: toponymy, folklore, fairytale teaching materials, Parigi Sub-District Pangandaran District.